1992
DOI: 10.1159/000107013
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinergic Model of Dementia, Alzheimer Type: Progression from the Unitary Transmitter Concept

Abstract: Efforts continue toward the goal of uncovering a dominant pathogenetic and therapeutic model for Alzheimer type dementia. This article critically reviews the evolution and current status of unitary transmitter concepts, the prototype of which is the cholinergic model proposed by Deutsch and others, from early animal studies to ongoing drug trials. We conclude that evidence is sufficient to dismiss such models as a means of directing treatment and further resources. A survey of novel approaches to Alzheimer typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
(73 reference statements)
1
16
0
Order By: Relevance
“…The hypothesis that stresses the significance of aberrations in the functions of cortical cholinergic inputs for the development of cognitive dysfunctions and the associated focus on the development of pharmacological treatments acting via cholinergic mechanisms have been discussed critically in recent years [152,153]. These criticisms have been primarily based on (1) the limited potency of muscarinic antagonists to produce the symptoms of dementia, (2) the failure of conventional cholinomimetic drugs to enhance cognitive functions or to attenuate age-or dementia-related cognitive impairments and, in this context, (3) the rejection of the idea that attentional abnormalities, which represent the primary consequence of cholinergic dysfunction, are sufficiently potent to account for the emergence of clinical syndromes.…”
Section: Age-related Decline In the Function Of Cortical Cholinergic mentioning
confidence: 99%
“…The hypothesis that stresses the significance of aberrations in the functions of cortical cholinergic inputs for the development of cognitive dysfunctions and the associated focus on the development of pharmacological treatments acting via cholinergic mechanisms have been discussed critically in recent years [152,153]. These criticisms have been primarily based on (1) the limited potency of muscarinic antagonists to produce the symptoms of dementia, (2) the failure of conventional cholinomimetic drugs to enhance cognitive functions or to attenuate age-or dementia-related cognitive impairments and, in this context, (3) the rejection of the idea that attentional abnormalities, which represent the primary consequence of cholinergic dysfunction, are sufficiently potent to account for the emergence of clinical syndromes.…”
Section: Age-related Decline In the Function Of Cortical Cholinergic mentioning
confidence: 99%
“…As reviewed previously by Holttum and Gershon [72], the cholinergic model proposed to explain the pathophysi ology of AD explains too little of the neuropathological data available. In that review they concluded that se lective cholinergic agents did not prove to be effective in the treatment of AD.…”
Section: Discussionmentioning
confidence: 99%
“…DuP996, an M 2 -receptor antagonist, is thought to increase the release of ACh, as well as other neuromodulators such as serotonin, by modulation of potassium channels in the synaptic terminals [45]. Improvements in subjects with impaired learning have been demonstrated with a galanin antagonist that disinhibits the release of ACh in experimental studies [46].…”
Section: Presynaptic Acetylcholine Release (Receptor Antagonists)mentioning
confidence: 99%
“…The wellknown neurodegenerative 'sprouting' phenomenon of remaining septohippocampal cholinergic fibres [57] may explain why recognition memory, which is dependent on temporal lobe function, is less amenable to tacrine therapy than the attentional deficit in AD patients, which is thought to be dependent upon frontal lobe function [55] where sprouting has not been demonstrated. Additionally, tacrine is associated with a poor side-effect profile, including hepatotoxicity, which results in a large proportion of patients discontinuing therapy [45,58]. Consequently, more specific, potent and tolerable ChE inhibitors are becoming available [50].…”
Section: Muscarinic and Nicotine Receptor Agonists (Direct Postsynaptmentioning
confidence: 99%